Draft genome of the American Eel (Anguilla rostrata). (14th November 2016) - Pavey, Scott A.; Laporte, Martin; Normandeau, Eric; Gaudin, Jérémy; Letourneau, Louis; Boisvert, Sébastien; Corbeil, Jacques; Audet, Céline; Bernatchez, Louis
Abstract: Freshwater eels ( Anguilla sp.) have large economic, cultural, ecological and aesthetic importance worldwide, but they suffered more than 90% decline in global stocks over the past few decades. Proper genetic resources, such as sequenced, assembled and annotated genomes, are essential to help plan sustainable recoveries by identifying physiological, biochemical and genetic mechanisms that caused the declines or that may lead to recoveries. Here, we present the first sequenced genome of the American eel. This genome contained 305 043 contigs (N50 = 7397) and 79 209 scaffolds (N50 = 86 641) for a total size of 1.41 Gb, which is in the middle of the range of previous estimations for this species. In addition, protein‐coding regions, including introns and flanking regions, are very well represented in the genome, as 95.2% of the 458 core eukaryotic genes and 98.8% of the 248 ultra‐conserved subset were represented in the assembly and a total of 26 564 genes were annotated for future functional genomics studies. We performed a candidate gene analysis to compare three genes among all three freshwater eel species and, congruent with the phylogenetic relationships, Japanese eel ( A. japanica ) exhibited the most divergence. Overall, the sequenced genome presented in this study is a crucial addition to the presently available genetic tools to help guide future conservation efforts of freshwater eels.